Vibrations of the S1 state of fluorobenzene-h5 and fluorobenzene-d5 via resonance-enhanced multiphoton ionization (REMPI) spectroscopy - Harris, Joe P.; Andrejeva, Anna; Tuttle, William D.; Pugliesi, Igor; Schriever, Christian; Wright, Timothy G. (American Institute of Physics, 2014)
We report resonance-enhanced multiphoton ionization spectra of the isotopologues fluorobenzeneh5 and fluorobenzene-d5. By making use of quantum chemical calculations, the changes in the wavenumber of the vibrational modes upon deuteration are examined. Additionally, the mixing of vibrational modes both between isotopologues and also between the two electronic states is discussed. The isotopic shifts lead to dramatic changes in the appearance of the spectrum as vibrations shift in and out of Fermi resonance. Assignments of the majority of the fluorobenzene-d5 observed bands are provided, aided by previous results on fluorobenzene-h5.